Lung ultrasound compared to chest X‐ray for diagnosis of pediatric pneumonia: A meta‐analysis. Issue 8 (26th April 2018) - Balk, Daniel S.; Lee, Christine; Schafer, Jesse; Welwarth, Jeremy; Hardin, John; Novack, Victor; Yarza, Shaked; Hoffmann, Beatrice
Abstract: Objective: Although a clinical diagnosis, the standard initial imaging modality for patients with concern for pediatric community acquired pneumonia (pCAP) is a chest x‐ray (CXR), which has a relatively high false negative rate, exposes patients to ionizing radiation, and may not be available in resource limited settings. The primary objective of this meta‐analysis is to evaluate the accuracy of lung ultrasound (LUS) compared to CXR for the diagnosis of pCAP. Methods: Data were collected via a systematic review of PubMed, EMBASE, and Web of Science with dates up to August 2017. Keywords and search terms were generated for pneumonia, lung ultrasound, and pediatric population. Two independent investigators screened abstracts for inclusion. PRISMA was used for selecting appropriate studies. QUADAS was applied to these studies to assess quality for inclusion into the meta‐analysis. We collected data from included studies and calculated sensitivity, specificity, positive predictive value, and negative predictive values of CXR and LUS for the diagnosis of pCAP. Results: Twelve studies including 1510 patients were selected for data extraction. LUS had a sensitivity of 95.5% (93.6‐97.1) and specificity of 95.3% (91.1‐98.3). CXR had a sensitivity of 86.8% (83.3‐90.0) and specificity of 98.2% (95.7‐99.6). Variations between the studies included ultrasound findings diagnostic of pneumonia, study setting (inpatient vs emergency department) and inclusion of CXR in the reference standard for pneumonia. Conclusions: In our meta‐analysis, lung ultrasound had significantly better sensitivity with similar specificity when compared to chest x‐ray for the diagnosis of pediatric community acquired pneumonia.